1993
DOI: 10.1177/026835559300800205
|View full text |Cite
|
Sign up to set email alerts
|

Recurrence and Late Sequelae after First-Time Deep Vein Thrombosis: Relationship to Initial Signs

Abstract: Objective: To investigate the relation between initial symptoms and long-term sequelae in first-time deep venous thrombosis (DVT). Design: Follow-up study of patients 6 years after an episode of suspected symptomatic DVT. Setting: Vascular laboratory, University Hospital of Lund. Patients: 66 patients, 19 with femoral DVT, 20 with calf DVT and 27 with normal phlebograms at initial investigation. Main outcome measures: Symptoms and signs of chronic venous insufficiency (CVI), foot volumetry and measurement of p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0
1

Year Published

1996
1996
2002
2002

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(11 citation statements)
references
References 21 publications
1
9
0
1
Order By: Relevance
“…It is difficult to discount the possibility that a decreased Marder score did not coincide with a silent PE, since lung scans were only taken to assist diagnosis of symptomatic PE. However, the low 6month recurrence rates with dalteparin (3.1 %) and heparin (1.9 %) compared with those obtained by Lagerstedt et al who reported 8 % recurrence within 1 year and 28 % within 6 years [12], suggest that this was not a frequent occurrence, if indeed it happened at all. In the study by Prandoni et al [1] the incidence of new segmental defects after the initial treatment period was 5 % in the LMWH group and 19 % in the UFH group, all without any symptoms.…”
Section: Discussionmentioning
confidence: 58%
“…It is difficult to discount the possibility that a decreased Marder score did not coincide with a silent PE, since lung scans were only taken to assist diagnosis of symptomatic PE. However, the low 6month recurrence rates with dalteparin (3.1 %) and heparin (1.9 %) compared with those obtained by Lagerstedt et al who reported 8 % recurrence within 1 year and 28 % within 6 years [12], suggest that this was not a frequent occurrence, if indeed it happened at all. In the study by Prandoni et al [1] the incidence of new segmental defects after the initial treatment period was 5 % in the LMWH group and 19 % in the UFH group, all without any symptoms.…”
Section: Discussionmentioning
confidence: 58%
“…2 Several studies have shown that the incidence of the postthrombotic syndrome is quite equal when distal and more proximal DVTs are compared. [12][13][14] It has been argued that an isolated cDVT may be treated without anticoagulant therapy in cases with no propagation into proximal veins. 1,8 Several hemodynamic events may occur after DVT, but their significance to late outcome is poorly defined, such as propagation into proximal segments after cDVT, 6 reflux in the initially uninvolved segments, 10 and recurrent DVT.…”
Section: Discussionmentioning
confidence: 99%
“…29 Some caution is needed in interpreting the findings as 64% of the original cohort group was lost to follow-up.…”
Section: Epidemiology and Natural Historymentioning
confidence: 99%
“…In one prosecutive, controlled study, patients with proximal DVT had more pigmentation and pitting edema than control subjects or patients with distal DVT; however, symptoms of aching pain, morning swelling, itching, or the need to wear compression stockings were not different among the three groups. 29 Some caution is needed in interpreting the findings as 64% of the original cohort group was lost to follow-up.…”
Section: Epidemiology and Natural Historymentioning
confidence: 99%